UNDERWATER AUTONOMOUS VEHICLE (AUV) - CHIK ROS, ARIF FAHIMI (IRC, 2019)
For my Final Year Project, I had chosen a project which is to design a functioning prototype of Underwater Autonomous Vehicle. This project is basically a project which consist of combination from the electrical and mechanical part. For electrical part, some of the components will be used for this project to be success such as the pressure sensor for controlling the depth of the UAV when it submerged in the water. It also use GPS module to navigate this UAV. The most important things for this project is the motor which be used to move this UAV forward, backward and also turning. For it to go upward and downward, it will used the ballast tank. For the designing of the prototype, Autodesk Inventor will be used before fabricate it. After it completed, then all of the component will be integrated including the programmed microcontroller, motors and others for the UAV to functioning well.